(untitled) (Fiep Bulletin - online, 2019)
Introduction: Due to the comforts provided by modern life, the sedentary lifestyle today can be considered the disease ofthe millennium. We know that the number of women entering the labor market has grown more and more, especially in higherpositions in offices where work is done mostly on computers that require sitting. With this routine adiposity and edema tend to increasein lower limbs. Objective: to verify after the Modeling Massage and Manual Lymphatic Drainage, the results on body composition inlower limbs of female volunteers. Methodology: the study was carried out with four female volunteers with ages ranging from 25 to 35years, through four sessions each. Data compared before and after, using tape measure and data analysis with Physical EvaluationProgram and Prescription Physical Test 8.0 - Terrazul. Results: The results were computed from the MMII measurements of 4volunteers and presented by the BODY MAP and PHYSICAL TEST 8.0 evaluation system provided by Terra Azul Technologies. thefour volunteers obtained a more satisfactory result in the manual lymphatic drainage protocol compared to the modeling massage.Final considerations: The manual lymphatic drainage protocol presented greater efficacy in volumetric comparisons than modelingmassage. In the comparison between practice of Modeling Massage and Manual Lymphatic Drainage in the LLL, DLM presented amean decrease in (MID = - 0.7%) and (MIE = - 0.5).